Australian public policies regarding aboriginal affairs (1883-1972) : a bilateral perspective - Male, Tanguy Oliver René (2022)
From the Council for Aboriginal Reconciliation Act 1991, the importance of past acknowledgement regarding sufferings towards natives became a massive stakes. However contested by the History Wars, which is an ongoing debate opposing conservative and progressive historians about the treatment inflicted to First Nations, NSW Government started to interfere in indigenous affairs from 1883 and the creation of the Protection Board. From then on, we observe a political uniformization implemented by a Eurocentric bureaucratic system, giving white Australians a total control over aboriginal life. Despite activism, the colonial system did not intend to provide fair and equal rights for everyone. Indeed and regardless the Calvin’s Case, all English subjects could not pretend to self-determination. In the 1901 Constitution, section 51 (also known as the races power) mentions : “the people of any race, other than aboriginal race in any state, for whom it is deemed necessary to make special laws”. The creation of the Department of Aboriginal Affairs by the Whitlam government in 1972, following the Tent Embassy protest, marked the beginning of a new era. This dissertation aims to understand how unilateralism is explained by a lack of awareness towards cultural differences and the desire for political possession from the British Empire. On the other hand, several organizations intended to get recognition throughout different strikes, but also bringing international attention from the 50’s, influenced by Afro-American activism. Understanding the past and how First Nations became aliens in their own land, I wish to supply a comprehensive bilateral approach. A partir da Lei do Conselho para a Reconciliação Aborígene de 1991, a importância do reconhecimento do sofrimento passado em relação aos nativos tornou-se uma aposta maciça. No entanto contestado pelas Guerras Históricas, o Governo de NSW começou a interferir nos assuntos indígenas a partir de 1883 e a criação do Conselho de Proteção. A partir daí, observamos uma ...